2021
DOI: 10.29040/jiei.v7i1.1789
|View full text |Cite
|
Sign up to set email alerts
|

Pendayagunaan Zakat Pada Masa Pandemi Covid-19

Abstract: At this time, the world is in an irregular and chaotic condition due to the covid-19 virus, especially in the economic sector. This resulted in the community's economy becoming paralyzed so that the income of the poor was also affected. To restore the state's condition, cooperation from various elements is needed, one of which is bias through zakat management institutions. The optimal utilization and management of zakat will help the community besides that the distribution is carried out appropriately and payi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 1 publication
0
14
0
4
Order By: Relevance
“…On top of that, Saputra (2020) mentioned that zakat could play practical tools for society to respond to the pandemic crisis. Similarly, Amanda et al (2021) research confirmed that zakat could be a viable solution to overcome COVID-19. This view is also supported by Kadir et al (2020) concluded that the use of zakat funds for handling Covid-19 was following sharia and maqashid rules.…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…On top of that, Saputra (2020) mentioned that zakat could play practical tools for society to respond to the pandemic crisis. Similarly, Amanda et al (2021) research confirmed that zakat could be a viable solution to overcome COVID-19. This view is also supported by Kadir et al (2020) concluded that the use of zakat funds for handling Covid-19 was following sharia and maqashid rules.…”
Section: Introductionmentioning
confidence: 71%
“…Hal ini didukung dengan penelitian (Safitri & Huda, 2021), lembaga amil zakat menjadi solusi dalam meningkatkan pertumbuhan ekonomi ditengah pandemi covid-19. Sejalan dengan (Amanda et al, 2021), pendayagunaan zakat sangat membantu para terdampak covid-19 diantaranya sektor kesehatan, sektor sosial ekonomi dan sektor program eksisting. This is supported by Safitri & Huda (2021), mentioned that amil zakat institution becomes a solution in increasing economic growth during the covid-19 pandemic.…”
Section: Financial Performance Of Amil Zakat Institution Is Stable An...unclassified
See 1 more Smart Citation
“…Although research related to the management of zakat funds in this pandemic had been carried out by (Amanda et al, 2021) shows that zakat funds are distributed into three health emergency sectors, socio-economic emergency sectors, and based on existing programs. In addition, BAZNAS also helps preachers who have been affected by the Covid-19 virus.…”
Section: Introductionmentioning
confidence: 99%
“…However, East Kalimantan LAZ DPU. Based on the contradictory findings by Amanda et al (2021), Ansoriyah et al (2020), Baskoro & Karmanto (2020), Nurhidayat (2020). The researchers felt the need to review the management of zakat in East Kalimantan LAZ DPU, especially during the pandemic.…”
Section: Introductionmentioning
confidence: 99%